Pengaruh Komunikasi Kerja, Disiplin Kerja, dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Kasus : pada Beberapa Minimarket Indomaret di Wilayah Kabupaten Sidoarjo) - Vidarnako, Friska Helviana; Andriani, Dewi; Firdaus, Vera (Universitas Respati Indonesia, 2024)
The aim of this research is to determine the performance of Indomaret Minimarket Employees in the Sidoarjo Regency Region in developing employee performance. This research analyzes Work Communication on Employee Performance, Work Discipline on Employee Performance and Work Environment on Employee Performance. This research method uses quantitative research methods. using a sample determination technique using cluster sampling. The sample in this study consisted of 100 respondents. Data collection in this research was by distributing questionnaires to respondents using a manual questionnaire. The software is called SPSS. Data analysis techniques include testing standard assumptions and multiple linear regression analysis. In testing the hypothesis, the R2 test, t test and F test were used. The results of this research show that there is a significant and beneficial influence between Work Communication, Work Discipline and the Work Environment on Employee Performance. The partial influence of Work Communication has a positive and beneficial impact. Work Discipline has a positive and beneficial influence. Employee performance is positively and significantly influenced by the work environment. The Fcount value is 85.677 while > Ftable is 3.091 and < 0.05 (0.000 < 0.05). Thus, the variables of work communication, work discipline and work environment simultaneously have a significant effect on employee performance.